1999
DOI: 10.1021/jp991365c
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Phase Diagram for a Ternary System of Block Copolymer PS310-b-PAA52/Dioxane/H2O

Abstract: The partial ternary phase diagram was investigated for the polystyrene 310 -block-poly(acrylic acid) 52 copolymer in dioxane/water mixtures in regions in which self-assembled nanoaggregates of various morphologies are seen. Both fractionated and unfractionated copolymers were used; the unfractionated copolymer contains homopolystyrene. The study was carried out over the range of water contents from 0 to 45 wt % and copolymer concentrations from 0.1 to 10 wt %. Freeze-drying transmission electron microscopy (TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
481
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 378 publications
(512 citation statements)
references
References 56 publications
24
481
1
6
Order By: Relevance
“…14 It has been observed that the morphological changes from wormlike cylinders to vesicles in PBD 103 -b-PAA 75 occur via branched cylinders and a wormlike-cylinder network, 14 whereas in the case of the crew-cut morphology of PS 310 -b-PAA 52 in DMF/water, the change from cylinders to vesicles occurs without the formation of a network. 39 In our case (block copolymer PS 962 -b-PEO 227 ), when the solvent mixture is DMF/water, the change from cylinders to vesicles occurs via branched cylinders and the network, whereas in the DMF/acetonitrile solvent mixture, the change occurs without the formation of the network. Again, the solvent plays a crucial role in determining the morphological pathway of the change from cylinders to vesicles.…”
Section: Resultsmentioning
confidence: 69%
“…14 It has been observed that the morphological changes from wormlike cylinders to vesicles in PBD 103 -b-PAA 75 occur via branched cylinders and a wormlike-cylinder network, 14 whereas in the case of the crew-cut morphology of PS 310 -b-PAA 52 in DMF/water, the change from cylinders to vesicles occurs without the formation of a network. 39 In our case (block copolymer PS 962 -b-PEO 227 ), when the solvent mixture is DMF/water, the change from cylinders to vesicles occurs via branched cylinders and the network, whereas in the DMF/acetonitrile solvent mixture, the change occurs without the formation of the network. Again, the solvent plays a crucial role in determining the morphological pathway of the change from cylinders to vesicles.…”
Section: Resultsmentioning
confidence: 69%
“…This agree with the experimental results qualitatively. Shen and Eisenberg [49,50] reported that by controlling solvent condition, one can control the morphology of the block copolymer micelles. The control of the morphology is especially important for application use such as the drug delivery system.…”
Section: Resultsmentioning
confidence: 99%
“…The polymerization index of PS-PEO diblock copolymer used in the experiments [51] is typically ≃ 1000, thus we expect that χ PS,PEO N is sufficiently larger than the critical value χ c N = 10.495 [14]. Note that the polyelectrolytes such as poly(acrylic acid) (PAA) is often used as the hydrophilic subchian [49,50]. Such polyelectrolytes can be dissolved into water easily, and thus we expect the χ parameter between the polyelectrolytes and the water is negative.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…The dependence of the morphology on the concentration can be seen very clearly in the phase diagram (discussed later). 43 Shen and Eisenberg 41 showed that in the phase diagrams for different PS-b-PAA copolymer systems, when the water content is at a fixed value, the initial copolymer concentration is important in determining if vesicles can be formed. For example, at a fixed water content of 25 wt %, vesicles only form at concentrations greater than approximately 0.6 wt % PS 310 -b-PAA 52 copolymer.…”
Section: Copolymer Composition and Concentrationmentioning
confidence: 99%